The Unofficial Harry Potter Cookbook : From Cauldron Cakes to Knickerbocker Glory--More Than 150 Magical Recipes for Wizards and Non-Wizards Alike - Bucholz, Dinah (Avon, Mass. : Adams Media, 2010)
A collection of recipes for foods mentioned in the Harry Potter series, including Kreacher's French onion soup, mashed parsnips, and treacle pudding, accompanied by short passages showing when the food appeared in the books.
Good food with bad relatives -- Delights down the alley -- Treats from the train -- Recipes from a giant and an elf -- The favorite cook's dishes -- Breakfast before class -- Lunch and dinner in the dining hall -- Desserts and snacks at school -- Holiday fare -- Treats in the village.
Includes bibliographical references (p. 231-233) and index.
Keywords: Rowling, J. K. -- Characters -- Harry Potter -- Juvenile literature; Rowling, J. K. -- Characters -- Harry Potter; Rowling, J. K -- Characters; Cooking, English -- Juvenile literature; Potter, Harry (Fictitious character) -- Juvenile literature; Cooking, English; Potter, Harry (Fictitious character); English cooking; Potter, Harry (Fictional character)